Recent Research Progress of Chiral Small Molecular Antitumor-Targeted Drugs Approved by the FDA From 2011 to 2019 - Chu, Xuetong; Bu, Yizhi; Yang, Xiaoping (Frontiers in Oncology, 2021)
Chiral drugs usually contain chiral centers, which are present as single enantiomers or racemates. Compared with achiral drugs, they have significant advantages in safety and efficacy with high stereoselectivity. Of these drugs, chirality not only exerts influence on the solubility and pharmacokinetic characteristics but also has specific mechanistic characteristics on their targets. We noted that small molecules with unique chiral properties have emerged as novel components of anti-tumor drugs approved by FDA in decade. Since approved, these drugs have been continuously explored for new indications, new mechanisms and novel combinations. In this mini review, recent research progress of twenty two FDA-approved chiral small molecular targeted anti-tumor drugs from 2011 to 2019 is summarized with highlighting the potential and advantages of their applications. We believe that these updated achievements may provide theoretical foundation and stimulate research interests for optimizing drug efficacy, expanding clinical application, overcoming drug resistance and advancing safety in future clinical administrations of these chiral targeted drugs.